Huang Huang. The Cooperative Principle Based Study on Passive Sentence Translation in Science and Technology English—To Improve the Quality and Efficiency of Non Literature Translation: “O‘zbek filologiyasining dolzarb masalalari va uni o‘qitish metodikasi muammolari” mavzusidagi Xalqaro ilmiy – amaliy anjuman 2022 yil 29 aprel Toshkent.: VNESHINVESTPROM, 2022 - Jurayev, Jamoliddin (FILOLOGIYA UFQLARI JURNALI, 2022)
In recent years, technology has developed rapidly, and more and more transnational cooperative organizations have emerged, where developers from different countries work together to solve different problems and create high-tech products. In this particular work environment, sometimes developers from different countries who speak different languages need to use a second language to communicate with their colleagues.